State of the Art and Challenges for Offshore Integrated Multi-Trophic Aquaculture (IMTA) - Buck, Bela H.; Troell, Max F.; Krause, Gesche; Angel, Dror L.; Grote, Britta; Chopin, Thierry (Frontiers in Marine Science, 2018)
By moving away from coastal waters and hence reducing pressure on nearshore ecosystems, offshore aquaculture can be seen as a possible step towards the large-scale expansion of the marine food production. Integrated multi-trophic aquaculture (IMTA) in nearshore water bodies has received increasing attention and could therefore play a role in the transfer of aquaculture operations to offshore areas. IMTA holds scope for multi-use of offshore areas and can bring environmental benefits from making use of waste products and transforming these into valuable co-products. Furthermore, they may act as alternative marine production systems and provide scope for alternative income options for coastal communities, e.g. by acting as nodes for farm operation and maintenance requirements. This paper summarizes the current state of knowledge on the implications of the exposed nature of the offshore and open ocean sites on the biological, technological and socio-economic performance of IMTA. Of particular interest is improving knowledge about resource flows between integrated species in hydrodynamic challenging conditions that characterise offshore waters.